Occupational practice in patients with hereditary transthyretin amyloidosis, a qualitative study - Aina Gayà-Barroso; Juan González-Moreno; Adrián Rodríguez; Tomás Ripoll-Vera; Inés Losada-López; Margarita Gili; Milena Paneque; Sara Pérez-Martínez; Eugenia Cisneros-Barroso (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Hereditary transthyretin amyloidosis (ATTRv) is a rare genetic disease that negatively affects patients' quality of life through the involvement of various organs and tissues. Despite a large amount of research on medical and psychosocial interventions, the impact of occupational therapy (OT) on patients with ATTRv is not well understood. Objective The aim of this study was to develop an OT programme to improve the daily functioning and quality of life of patients with ATTRv. Methods Fourteen patients with ATTRv were interviewed. Together they developed short- and medium-term occupational goals. Patients received the OT intervention for six months. Outcomes were measured using scores for activities of daily living and psychological well-being. Results The study found that OT can have a positive impact as a complementary intervention to medical and other psychosocial treatments. Of the 14 patients, 12 maintained the same scores in activities of daily living. Two deteriorated and eight improved their psychological scores. Conclusion This study highlights the need for further research in this area and the importance of OT in the management of patients with ATTRv. Early intervention is of paramount importance and further research is needed to evaluate the long-term effects of OT interventions in patients with ATTRv.